POTATO MOP TOP VIRUS- AN EMERGING THREAT TO THE POTATO CROP WORLD WIDE - Rashmi Mishra, Shivansh Verma, Soni Kumari, Sahil Rustagi, Pratibha Pandey, Fahad Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Increase in the concern of potato diseases induced by various pathogenic bacteria, nematodes, fungi, viruses which reduces the quality and yield of Potato. Potato Mop Top Virus(PMTV), first incidence was reported in 1966, within the boundaries of Andean Region of South America then spread throughout the world and causes significant loss to the economy. PMTV has a rod-shaped, tubular structure containing tripartite positive-sense ssRNA genome structure. With the advancement in detection techniques such as microplate hybridization, widely used Reverse Transcription Polymerase Chain Reaction and Enzyme-Linked ImmunoSorbent Assay, and fluorescent amplification-based specific hybridization have successfully improved the detection of PMTV . Some studies suggest that interaction between the different segments of PMTV genome with some transport factor protein of plants that plays a key role in systemic movement and viral cell- to- cell movement. Databases result analysissuggeststhatPMTVsequencesshowhighsimilarityamongdifferentcountries isolates of potato. Tolerant cultivars are widely studied to suggest some agronomic characteristics which can be employed by commercial cultivars and will be combined with those cultivars which show the absence of symtopms such as tuber necrosis or little accumulation of Potato Mop top virus. Previous studies suggest that moisture of soil also play sacrucial role in developing the PMTV tuber symptoms and necrosis and thus improvement in irrigation management schemes may reduce the disease pressure. This review aims to present the detrimental effect on Potatoes worldwide by PMTV and by itsvector.